Who graduates from drug courts? Correlates of client success - Hartley, Roger E. (American journal of criminal justice, 2001)
Drug courts combine punishment and treatment to provide an intermediate sanction for offenders. This paper contains an analysis of drug court case files for 196 participants in one mid-Atlantic jurisdiction. Logistic regression reveals that employment status before and during the program, race, education, and referral time are significant predictors of successful completion. Policy implications and suggestions about participant screening and program administration are offered.